Mengenal literasi digital dan hoaks di Desa Mandiangin Kabupaten Siak - Tantri Puspita Yazid; Salsabila Salsabila (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
The first phenomenon that underlies the importance of this multidisciplinary community service is related to the phenomenon of hoaxes. In general, media literacy is needed to be able to understand the messages they receive, how to find the right messages, and how to deal with them. Education certainly plays an important role for the younger generation who are the real targets of today's exposure to technology and digitalization. Mandiangin Village, which has problems at the education level, is the target of socialization and empowerment for students in Mandiangin Village which is deemed appropriate. So, the community service activities carried out are educating students about digitalization and the importance of literacy. It aims to explore the community's understanding of digitalization and literacy as well as to advocate for students as the younger generation regarding tips for dealing with hoaxes. Through this community service activity, especially on the first theme, namely recognizing digital literacy, it can be concluded that students have been able to know and understand the importance of digital literacy and respond to hoaxes